HUBUNGAN INFORMASI SILPA APBD DAN ARUS KAS DENGAN PENGANGGARAN BELANJA MODAL PADA PEMERINTAH DAERAH - Moh Syadeli (Politeknik Negeri Malang, 2018)
This study aims to test and analyze the influence of the SiLPA APBD, Operating Cash Flow, Investment Cash Flow, funding cash flows on capital expenditure budgeting. The source of this research data is the district and city financial statements that exist in the NTT provincial government within a period of 5 years, from 2012-2016. This study uses 2 variables, namely independent and bound variables. The independent variable consists of SiLPA APBD information, Operating Cash Flow (CFO), Investment Cash Flow (CFI) and Funding Cash Flow (CFF), while the dependent variable consists of capital expenditure. The results of this study are that simultaneously the four independent variables have a significant effect on capital expenditure budgeting, partially the four independent variables also have a significant effect on capital expenditure budgeting and the most dominant is the CFI (X3) or Investment Cash Flow variable.